American Executives' Perception of Foreign State Enterprises - Prasad, S. Benjamin (Journal of International Business Studies, 1986)
While Lamont (1979) and Monsen and Walters (1983) have taken a strong stance that foreign state enterprises are a threat to U.S. business, the question of how the senior level business executives in the U.S. firms view these companies in the 1980s remains unexplored. Executive perception of elements and events in the external environment are as important as facts and their interpretations. This research note reports the findings of a survey (questionnaire and telephone interviews) of 111 senior executives of U.S. firms and interprets the findings against the backdrop of the model of post-industrial organization expounded by Huber. The main finding of the survey is that in the mid-1980s the threat that loomed large in the minds of executives was rather ‘foreign imports’ than foreign state enterprises.